The Cyber Crime and Security Scenario in India: Understanding the challenges and trends in cybercrime prevention and investigation in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cybercrime is a borderless issue, comprising of criminal acts that are perpetrated online by utilizing electronic interchanges systems and information frameworks -, for example, crimes particular to the Internet, online extortion and imitation and illicit online substance. While the estimation of the cybercriminal economy all in all isn't exactly known, the misfortunes are thought to speak to billions of Euros for every year. The size of the issue is itself a danger to law authorization reaction ability. These dangers can have distinctive starting points - including criminal, politically propelled, psychological oppressor or state-supported assaults and additionally catastrophic events and unexpected oversights. Cybercrime is expanding in scale and effect, yet there is an absence of dependable figures. Be that as it may, patterns recommend significant increments in scope, complexity number and kinds of assaults, number of casualties and monetary harm. Digital security occurrences, purposeful or coincidental, are expanding at a disturbing pace. This examination breaks down present issues &technical challenges for examination and avoidance of Cybercrimes in India.